In the shadow of the giant : the making of Mexico's Central America policy, 1876-1930 - Buchenau, Jürgen, 1964- (University of Alabama Press, 1996)
"Thorough study of the endogenous and external factors that have shaped Mexico's dealings with the Central American republics. Asserts that Mexico's policy has reflected both its status as a 'middle power' between Central America and the United States, and its desire to assert a leadership role in the region"--Handbook of Latin American Studies, v. 58.